1960
DOI: 10.1172/jci104081
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Phosphorus Homeostasis in the Parathyroidectomized Dog; Evaluation by Means of Ethylenediamine Tetraacetate and Calcium Tolerance Tests*

Abstract: In an experiment designed to determine whether or not homografts of parathyroid tissue would survive and function in millipore diffusion chambers, Wilson, Zollinger, Mahan and Brooks (1) subjected female mongrel dogs to parathyroidectomy either in two stages or as a single procedure. Twelve animals with transplants survived the acute postoperative period with its attendant severe hypocalcemia, but all required intensive parenteral calcium support for periods ranging from 19 to 78 days. This supportive therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
1

Year Published

1963
1963
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 10 publications
(7 reference statements)
4
18
1
Order By: Relevance
“…Nevertheless, the presence of a residual parathyroid activity cannot completely be excluded. It is well known that after transitory symptoms of parathyroid insufficiency, parathyroidectomized dogs recover after a few weeks a normal blood level of calcium (7) and cannot easily be distinguished from normal with regard to the renal excretion of phosphorus (8,9). The mechanism of the new homeostasis is not known.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the presence of a residual parathyroid activity cannot completely be excluded. It is well known that after transitory symptoms of parathyroid insufficiency, parathyroidectomized dogs recover after a few weeks a normal blood level of calcium (7) and cannot easily be distinguished from normal with regard to the renal excretion of phosphorus (8,9). The mechanism of the new homeostasis is not known.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the drain upon the plasma calcium imposed by such sequestration results in low levels in the blood. However, this explanation alone fails to indicate why the plasma calcium is not replenished from skeletal reserves, as happens after experimentally induced hypocalcaemia (Sanderson et al, 1960;Potts et al, 1971).…”
Section: Discussionmentioning
confidence: 98%
“…The hypocalcemia which resulted could readily be attributed to removal of the parathyroid glands; however, the impaired recovery of these animals from the effects of calcium infusions could not be readily explained by the prevailing concept of calcium regulation. Sanderson et ~~· (1960) did not realize the import of these findings. It remained for Copp and coworkers to evaluate the effects on systemic blood calQium of acute stimulation or suppression of parathyroid glandular activity.…”
mentioning
confidence: 90%